Optimalisasi Branding Konten Audio-Visual untuk Meningkatkan Promosi Wisata Desa Kebontunggul, Mojokerto - Andrianto, Novan (Unri Conference Series: Community Engagement, 2024)
This study aimed to enhance tourism promotion for Desa Kebontunggul, Mojokerto by optimizing the village's website and Instagram account (@lembahmbencirang.id). Employing a qualitative descriptive approach, this research analyzed existing content and identified potential improvements through the creation of creative and engaging audio-visual content. The findings revealed that the application of content marketing principles such as design, relevance, user experience, and tone can significantly improve promotional effectiveness. Furthermore, the study provided recommendations for content types that need to be enhanced to achieve better promotional outcomes. Through the optimization of social media, it is expected to increase the number of tourist visits to Desa Kebontunggul and contribute positively to the local economy. This research is relevant to the development of rural tourism post-pandemic, which increasingly relies on social media as a promotional tool.